THE IMPLEMENTATION OF TEAM ASSISTED INDIVIDUALIZATION (TAI) TYPE COOPERATIVE MODEL TO INCREASE LEARNING OUTCOMES IN WORK AND ENERGY - NUKY DESIANA, ELISA; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2018)
In the process of studying physics, there are several problems that often encountered such as physics is one of the subjects considered to be complicated by most students. In addition, teaching activities that are generally still focused on teachers (teacher centered) and students are given less opportunity to work together in completing the structured tasks given by teachers. From these problems, it can be applied cooperative model type Team Assisted Individualization (TAI) as an alternative solution that encourages students actively involved in understanding the concept of physics so that learning process becomes meaningful then learning outcomes can be improved.The purpose of this research are to describe the implementation of TAI type cooperative model and to describe the improvement of learning outcome from knowledge, attitude, and skill aspect. This research is a quantitative research with Control Group Pre-test Post-test Design. Subjects in this study are class X MIA 1 as experimental class and X MIA 2 as control class. Methods of data analysis are by using interview method, observation method, validation method and test method which is test method consist of pre-test and post-test. Based on the result of the research, it can be concluded that the implementation of TAI type cooperative model has done well and there is improvement of student learning outcomes better after applying TAI type cooperative model from knowledge, attitude and skill aspect than student learning outcomes applying the conventional model. Keywords: Cooperative Model, Team Assisted Individualization (TAI), learning outcomes, work and energy